تطوير كفايات أداء أعضاء هيئة تدريس اللغة العربية في الجامعات وانعكاساتها على تحقيق جودة البحث العلمي - Deea Ahmed Alkurd (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
The study aimed to identify the necessary competencies that should be enjoyed by a member of the faculty of the Arabic language and the need to develop the teaching methods used, as well as a proposed concept was developed to develop the competencies of the performance of members of the Arabic language faculty in light of achieving the quality of scientific research, and the study was applied to a sample of faculty members Teaching Arabic from a master's and doctoral degree in major universities in the governorates of Gaza (Islamic University - Al-Azhar University - Al-Aqsa University), and the results of the study showed that the reality of the competencies of the performance of members of the Arabic language teaching staff in universities meets a high level which contributes to achieving the quality of research Scientific as well as work The necessity of activating the cells of quality assurance in universities in order to contribute to spreading a culture of quality in scientific research. The study recommended that members of the teaching staff of the Arabic language should use more than one teaching method per lesson in consideration of individual differences between students